2016
DOI: 10.1136/openhrt-2016-000399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dual pulmonary vasodilator therapy in pulmonary arterial hypertension associated with congenital heart disease: a retrospective analysis

Abstract: BackgroundPatients with pulmonary arterial hypertension (PAH) are managed according to evidence-based treatment guidelines.Methods and resultsIn this single-centre retrospective analysis, we examined outcomes of patients with PAH caused by congenital heart disease (PAH-CHD) with respect to exercise capacity and survival of adults treated with either bosentan or sildenafil monotherapy or bosentan-sildenafil dual therapy between January 2007 and January 2014. Of the 82 patients analysed, 29 had Down syndrome; 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, upper respiratory tract infection and vomiting had a higher prevalence in group A participants. A retrospective analytical study also showed similar 17 However, a study with patients suffering from Eisenmenger syndrome showed that upfront combination therapy with bosentan and sildenafil was not superior to bosentan monotherapy concerning changes in 6MWD. 18 As such, the general approach regarding treatment is to observe and record clinical worsening, to guide the decision to escalate treatment only when necessary.…”
Section: Resultsmentioning
confidence: 78%
“…However, upper respiratory tract infection and vomiting had a higher prevalence in group A participants. A retrospective analytical study also showed similar 17 However, a study with patients suffering from Eisenmenger syndrome showed that upfront combination therapy with bosentan and sildenafil was not superior to bosentan monotherapy concerning changes in 6MWD. 18 As such, the general approach regarding treatment is to observe and record clinical worsening, to guide the decision to escalate treatment only when necessary.…”
Section: Resultsmentioning
confidence: 78%
“…During the study period, 70 patients were enrolled: 35 were assigned to sildenafil monotherapy (Group A), and 17 However, a study with Eisenmenger syndrome patients found that upfront combination therapy with Bosentan and sildenafil was not superior to Bosentan monotherapy in terms of changes in 6MWD. 18 As a result, the general treatment approach is to observe and record clinical worsening in order to guide the decision to escalate treatment only when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings emerged from a retrospective analytical investigation as well. 17 However, a trial with individuals who had Eisenmenger syndrome revealed that bosentan monotherapy was not more effective than upfront combined therapy with sildenafil for changes in 6MWD. 18 Therefore, the fundamental therapeutic approach is to monitor clinical deterioration and analyze it to determine whether to step up treatment.…”
Section: Discussionmentioning
confidence: 99%